Distribution of grey wolves Canis lupus lupus in the Nepalese Himalaya: implications for conservation management. Issue 3 (7th July 2016) - Subba, Samundra Ambuhang; Shrestha, Anil Kumar; Thapa, Kanchan; Malla, Sabita; Thapa, Gokarna Jung; Shrestha, Sujeet; Shrestha, Shrota; Subedi, Naresh; Bhattarai, Gopal Prakash; Ottvall, Richard
Abstract: The grey wolf Canis lupus lupus is Critically Endangered in Nepal, and is a protected species there. Understanding the species' status and distribution is critical for its conservation in the Nepalese Himalaya. We assessed the distribution of the grey wolf in the Himalayan and Trans-Himalayan regions using data from faecal and camera trap surveys and published data sources. We recorded 40 instances of wolf presence. Using these data we estimated a distribution of 28, 553 km 2, which includes potential as well as known habitat and comprises 73% of the Nepalese Himalaya. There is evidence of recovery of the grey wolf population in Kanchenjunga Conservation Area in the eastern portion of the species' range. A livestock insurance scheme has been shown to be a viable option to reduce retaliatory killing of wolves as a result of livestock depredation. The wolf plays an important ecological role in the Himalaya, and its conservation should not be delayed by the ongoing taxonomic debate about its subspecific status.